2017
DOI: 10.18632/oncotarget.22639
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponins A, C and D enhance liver-targeting effects of anticancer drugs by modulating drug transporters

Abstract: Vinegar-baked Radix Bupleuri (VBRB) is clinically used to enhance the pharmacological activity of drugs used to treat liver diseases. Our previous study demonstrated that this effect is dependent on increased drug accumulation in the liver; however, the underlying mechanism remains unclear. We hypothesize that VBRB mediated its effects by altering drug transporters. Thus, the present study was designed to determine the effects of VBRB's main components, saikosaponin A, C, and D, on drug transporters. Transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The most popular source of it, B. chinense, is rich in triterpenoid saikosaponins (Wang et al 2018). Modern pharmacological research shows that saikosaponins isolated from B. chinense such as saikosaponin a (SSa), saikosaponin c (SSc), and saikosaponin d (SSd) have significant antiinflammatory (Chen et al 2018), antidepressant , antitumor (Feng et al 2017), hepatoprotective (Ashour and Wink 2011) and immunomodulatory (Yen et al 2010) effects, with a broad application foreground and high development potential.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular source of it, B. chinense, is rich in triterpenoid saikosaponins (Wang et al 2018). Modern pharmacological research shows that saikosaponins isolated from B. chinense such as saikosaponin a (SSa), saikosaponin c (SSc), and saikosaponin d (SSd) have significant antiinflammatory (Chen et al 2018), antidepressant , antitumor (Feng et al 2017), hepatoprotective (Ashour and Wink 2011) and immunomodulatory (Yen et al 2010) effects, with a broad application foreground and high development potential.…”
Section: Introductionmentioning
confidence: 99%
“…Saikosaponins exert significant pharmacological activities, including antitumor, chemosensitizing, radiosensitizing, anti‐inflammatory, hepatoprotective, nephroprotective, anti‐Alzheimer, neuroprotective, immune‐modulatory, anti‐virus, and so on. Saikosaponins are considered to be the major bioactive ingredients and the key markers for quality control of Radix Bupleuri , which is a famous traditional Chinese medicine (TCM) that has been used for more than 1000 years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to our findings, there are still a lot interesting points worth further study. Previous studies in cancer treatment suggested that saikosaponins (SSa, SSb, SSc, SSd) be potent adjuvant that are able to override primary drug resistance [42][43][44], improve sensitivity to chemotherapy and radiotherapy [45][46][47], and enhance liver-targeting effects of anticancer drugs [48]. For chronic HBV therapy, various drug combination therapies have been tried.…”
Section: Discussionmentioning
confidence: 99%